Tensors, their Variants, and Operations - Adhikari, Iswar Mani (AWADHARANA, 2024)
Tensors are mathematical objects that can describe physical properties like scalars and vectors. Tensors are the generalization of scalars and vectors; a scalar is a zero-rank tensor, and a vector is a first-rank tensor where the rank or the order of a tensor is defined by the number of directions required to describe it. In this paper, the focus is to insight into different fundamental tensors, their variants, and operations.